The Filipino can ; Accident or murder ; Flying high [videorecording] - Lazaro, Cheche (The Probe Team, 1991)
The Philippines finishes the SEA Games in second overall with 91 gold medal haul. A bus runs over a 13 year old boy in Ozamis. But people there say, Lilian Bus Lines has a policy of "atrasan" to make sure victims die to save on survivors that cost more. A story about excellence and the advances made by aircraft technology. Features the Lufthansa, the German Airline.